Intracellular superoxide level controlled by manganese superoxide dismutases affects trichothecene production in Fusarium graminearum. Issue 21 (5th October 2017) - Furukawa, Tomohiro; Yoshinari, Tomoya; Sakuda, Shohei
Abstract: The intracellular superoxide level is a clue to clarification of the regulatory mechanism for mycotoxin production in Fusarium graminearum . In this study, we focused on two manganese superoxide dismutases (SODs) of the fungus, FgSOD2 and FgSOD3, to investigate the relationship of the superoxide level to trichothecene production. Recombinant FgSOD2 and FgSOD3 showed SOD activity, and they were localized mainly in the mitochondria and cytoplasm, respectively. Trichothecene production and mRNA levels of Tri5 and Tri6, which encode a trichothecene biosynthetic enzyme and a key regulator of trichothecene production, respectively, were greatly reduced in gene-deletion mutants of FgSod2 and FgSod3 (Δ FgSod2 and Δ FgSod3 ). Significant increases in the cytosolic and mitochondrial superoxide levels were observed in Δ FgSod2 and Δ FgSod3, respectively. These results suggested that the cellular superoxide level affects trichothecene production in F. graminearum . Abstract : This study describes the impact of deletion of manganese superoxide dismutase genes on mitochondrial and cytosolic superoxide levels and trichothecene production in Fusarium graminearum .